ECOLOGIA E PROJEÇÃO DIAMÉTRICA DE TRÊS GRUPOS ARBÓREOS EM REMANESCENTE DE FLORESTA OMBRÓFILA MISTA EM SÃO FRANCISCO DE PAULA, RS - Ebling, Angelo Augusto; Péllico Netto, Sylvio; Watzlawick, Luciano Farinha; Veiga de Miranda, Rodrigo Otávio; Abrão, Simone Filipini (Floresta, 2013)
A Floresta Ombrófila Mista desempenha importante função social e ecológica na região Sul do Brasil. Embora tenha sofrido um profundo processo exploratório, resultando em sua fragmentação, apresenta elevado potencial para o manejo que, devidamente aplicado, favorece a conservação e recuperação de seus remanescentes. Com o objetivo de avaliar o incremento diamétrico e a dinâmica sucessional dessa fitofisionomia, foram empregados dados oriundos do estrato arbóreo (DAP ≥9,5 cm) de 10 parcelas permanentes de 1 ha cada, remedidas anualmente entre o período de 2000 a 2009, na Floresta Nacional de São Francisco de Paula, RS. As observações e projeções indicaram gradual redução da densidade da floresta, com destaque para a espécie Araucaria angustifolia (Bertol.) Kuntz., entretanto, observou-se tendência de aumento na densidade da família Lauraceae. O período de meia vida estimado para a floresta foi de 97 anos e, para Araucaria angustifolia, 332 anos. As estimativas ainda sugerem que, em 71 anos, as espécies de Lauraceae devem duplicar sua densidade. O crescimento da floresta foi inferior ao da família Lauraceae <!--[if supportFields]> QUOTE <![if gte msEquation 12]><span style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal" mce_style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal"><m:e><m:r>IPD</m:r></m:e><![endif]><![if !msEquation]><span style='font-size:11.0pt;line-height:115%;font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri;mso-bidi-font-family:"Times New Roman"; position:relative;top:4.0pt;mso-text-raise:-4.0pt;mso-ansi-language:PT-BR; mso-fareast-language:EN-US;mso-bidi-language:AR-SA'> <![endif]> <![endif]--><!--[if supportFields]><![endif]-->(<!--[if gte msEquation 12]><span style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal" mce_style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal"><m:e><m:r>IPD </m:r></m:e><![endif]--><!--[if !msEquation]--><!--[endif]-->= 0,175 cm/ano e <!--[if gte msEquation 12]><span style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal" mce_style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal"><m:e><m:r>IPD </m:r></m:e><![endif]--><!--[if !msEquation]--><!--[endif]-->= 0,179 cm/ano, respectivamente) e a Araucaria angustifolia manteve o menor crescimento (<!--[if gte msEquation 12]><span style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal" mce_style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal"><m:e><m:r>IPD </m:r></m:e><![endif]--><!--[if !msEquation]--><!--[endif]-->= 0,159 cm/ano). As análises indicaram um avanço sucessional, com a gradual substituição da Araucaria angustifolia por espécies com maior adaptação às condições de equilíbrio. Palavras-chave: Família Lauraceae; Floresta com Araucária; sucessão florestal. Abstract Ecology and diametric projection of three arboreal groups in a Mixed Ombrophilous Forest fragment in São Francisco de RS, Brazil. The Mixed Ombrophylous Forest performs an important social and ecological function in southern Brazil. Although it has suffered a profound exploratory process, resulting in their fragmentation, it has a high potential for management that, properly applied, promotes conservation and recovery of their remains. In order to assess the increment in diameter and dynamics of phytophisiognomy, this research used data from the tree strata (DBH≥9.5 cm) of 10 permanent plots of 1 ha each remeasured annually between the period 2000 to 2009 in São Francisco de Paula National Forest, RS, Brazil. The observations and projections indicate a gradual reduction in the forest density, showing up Araucaria angustifolia (Bertol.) Kuntze species, however, for the Lauraceae species, there was a tendency of increase. The period of half-life estimated for the forest was 97 years and for Araucaria angustifolia, 332 years. The estimates also suggested that in 71 years, the Lauraceae should double its density. The forest growth was lower than that observed in the Lauraceae (<!--[if gte msEquation 12]><span style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal" mce_style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal"><m:e><span lang=EN-US style="font-size:9.0pt;line-height:95%;font-family:"Cambria Math","serif"; letter-spacing:-.1pt;mso-ansi-language:EN-US" mce_style="font-size:9.0pt;line-height:95%;font-family:"Cambria Math","serif"; letter-spacing:-.1pt;mso-ansi-language:EN-US"><m:r>IPD</m:r></m:e><![endif]--><!--[if !msEquation]--><!--[endif]-->=0.175 cm/year and <!--[if gte msEquation 12]><span style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal" mce_style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal"><m:e><span lang=EN-US style="font-size:9.0pt;line-height:95%;font-family:"Cambria Math","serif"; letter-spacing:-.1pt;mso-ansi-language:EN-US" mce_style="font-size:9.0pt;line-height:95%;font-family:"Cambria Math","serif"; letter-spacing:-.1pt;mso-ansi-language:EN-US"><m:r>IPD</m:r></m:e><![endif]--><!--[if !msEquation]--><!--[endif]-->=0.179 cm/year, respectively) and Araucaria angustifolia maintained the lowest growth (<!--[if gte msEquation 12]><span style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal" mce_style="font-size:9.0pt;mso-ansi-font-size:9.0pt; mso-bidi-font-size:9.0pt;font-family:"Cambria Math","serif";mso-ascii-font-family: "Cambria Math";mso-hansi-font-family:"Cambria Math";letter-spacing:-.1pt; font-style:italic;mso-bidi-font-style:normal"><m:e><span lang=EN-US style="font-size:9.0pt;line-height:95%;font-family:"Cambria Math","serif"; letter-spacing:-.1pt;mso-ansi-language:EN-US" mce_style="font-size:9.0pt;line-height:95%;font-family:"Cambria Math","serif"; letter-spacing:-.1pt;mso-ansi-language:EN-US"><m:r>IPD</m:r></m:e><![endif]--><!--[if !msEquation]--><!--[endif]-->=0.159 cm/year). The analysis indicated a positive advance, with the gradual replacement of Araucaria angustifolia by other species with greater adaptation to the successional conditions. Keywords: Araucaria Forest; Lauraceae family; forest succession.